Evaluation of home type, abuse prevalence and care- perception on physical and emotional health among elderly people in South West, Nigera (2014)
Many countries may encounter a demographic change where the number of elderly people will increase. As a result, the number of very old people needing care, services and medical assistance will increase; Care in the private home is often described as providing the best alternative for many elderly people. The aim of this study was to evaluate elderly people's home type, different form of abuse experienced, perceptions of how they are cared for and its effect on their physical and emotional health. The was a survey research adopting expost facto research design. Multistage sampling technique was used to sample Three hundred and sixty elderly people living in a private home that participated in this study. Three instruments: Elderly Persons Care- Perception Questionnaire (EGPQ),r=0.87, Elderly Abuse Prevalence Questionnaire (EAPQ) r = 0.88 and A structured Interview with inter- rater reliability of 0.93 was used to collect data. Descriptive statistics (mean and standard deviation) and Multiple Regression Analysis was used to determine possible effect among variables. The result revealed a positive and significant relationship between abuse prevalence, carer perception (6 = 0.247, t(629) = 6.383, P < 0.05), Care-Perception (6 = - .047, t = .55, and physical and emotional health. Furthermore, nearly a quarter or 25% reported significant levels of psychological abuse of neglect which affected their physical and emotional health. It is therefore recommended that strategies to monitor abuse among elderly people be put in place while arrangement is made for public home caregivers to reduce prevalence of abuse.